2019
DOI: 10.11648/j.ijfet.20190302.13
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soy Protein Isolate, Starch and Salt on Quality of Ready-to-Eat Restructured Beef Products

Abstract: This experiment explored the effects of different additions of soy protein isolate, starch and salt on the quality characteristics of the ready-to-eat restructured beef products. The ground beef was used as the experimental material, and the different soy protein isolates, starch and salt were studied after conditioning and recombination. The product has the characteristics of thawing loss, yield, bond strength, texture and other quality characteristics. The results show that with the increase of the amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…After reducing sodium content, the Aw value of samples in all sodium-reduced groups (C2, F1 and F2) increased significantly (p < 0.05) compared with the control group C1, indicating that the binding of inner water and muscle fiber in the beef sample may be looser (Table 3). It led to the same opinion with the result previously reported [35], in which they found that the reduction of salt addition (0~2.5%) can significantly increase the water activity in restructured beef products.…”
Section: Water Activitysupporting
confidence: 86%
See 1 more Smart Citation
“…After reducing sodium content, the Aw value of samples in all sodium-reduced groups (C2, F1 and F2) increased significantly (p < 0.05) compared with the control group C1, indicating that the binding of inner water and muscle fiber in the beef sample may be looser (Table 3). It led to the same opinion with the result previously reported [35], in which they found that the reduction of salt addition (0~2.5%) can significantly increase the water activity in restructured beef products.…”
Section: Water Activitysupporting
confidence: 86%
“…This may be because that the fluidity restriction effect of water by Na + , and the binding of Cl − to positively charged groups in myofibrillar protein, both resulted in an increased electrostatic repulsion, reduced cohesion, and loose network structure of protein, which contributed to the binding of a large amount of non-flowing water by meat. Therefore, a decrease in salt content can increase the fluidity of water and decrease the water holding capacity [35].…”
Section: Lf-nmrmentioning
confidence: 99%
“…Diversifying how pigeon peas are utilized in the food industry could be one way to enhance their production, marketing, and consumption. One of the recommended applications is processing its protein into a binder for meat-based products like sausages ( Li, 2019 ) to replace soybean and chemical phosphate binders, which have been associated with health issues like renal, liver, and allergic reactions ( Inetianbor et al., 2015 ; Ritz et al., 2012 ). Pea protein appears to be a promising substitute due to its high nutritional protein content and non-allergenic qualities ( Lam.…”
Section: Introductionmentioning
confidence: 99%
“…It has been commonly consumed in the human diet because this plant has the highest percentage of protein, up to 24%, and is especially a rich source of lysine [ 13 ]. Various reports have shown that pigeon pea can be used as a novel ingredient in restructured meat products [ 14 , 15 ]. It is also used as a substitute for wheat flour to improve the nutritional value of biscuits [ 16 ] and crackers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%